Modul Pelatihan Project Based Learning Berbasis Google Workspace dalam Manajemen Kurikulum Merdeka - Tesalonika, Asry; Dwikurnaningsih, Yari; Ismanto, Bambang (Jurnal Pendidikan Indonesia, 2022)
Since entering the 21st century, the curriculum in Indonesia has continued to innovate to realize student-centered learning through the Merdeka Curriculum. To achieve this, teachers need to have competence in the use of technology to facilitate students to be able to achieve 21st-century skills through project-based learning. This study developed a training module for project-based learning with Google Workspace in the Merdeka Curriculum management. The research and development model refers to the Borg and Gall steps, including: information gathering, planning, preliminary product development, preliminary field testing, main product revisions, main field trials, and operational product revisions. This study uses a mixed method with a sequential exploratory design. The results show that the validity of the training materials is 73.33% in the feasible category, the validity of the training module reaches 90% in the very feasible category, and the validity of the media reaches 77% in the feasible category. The preliminary field trial was conducted with a percentage of readiness of 86.75%. The main field trial shows a percentage of readiness of 91.63%. The resulting training module has the advantage that it can be accessed anytime and anywhere and can be applied in training for teachers independently or in groups.